2022
DOI: 10.1186/s12951-022-01395-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional metal-organic frameworks: from synthesis to bioapplications

Abstract: As a typical class of crystalline porous materials, metal–organic framework possesses unique features including versatile functionality, structural and compositional tunability. After being reduced to two-dimension, ultrathin metal-organic framework layers possess more external excellent properties favoring various technological applications. In this review article, the unique structural properties of the ultrathin metal-organic framework nanosheets benefiting from the planar topography were highlighted, invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 112 publications
(116 reference statements)
0
16
0
Order By: Relevance
“…47 In comparison to the MOFs, metal-organic layers (MOLs) offer better ductility, light transmission, and large surface area and are, therefore, one of the areas of choice for clinical research. 85 In their report, Luo et al found that the photosensitizer could be isolated by fixing it in the 3D spatial skeleton of the MOFs, thus avoiding the aggregation of the photosensitizer, which could lead to sudden inactivation. They hypothesized that the use of 2D-MOFs, i.e., MOLs, due to their two-dimensional structure, could potentially improve the efficiency of 1 O 2 diffusion generated by the photosensitizer and thus improve the efficacy of PDT.…”
Section: Application In Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…47 In comparison to the MOFs, metal-organic layers (MOLs) offer better ductility, light transmission, and large surface area and are, therefore, one of the areas of choice for clinical research. 85 In their report, Luo et al found that the photosensitizer could be isolated by fixing it in the 3D spatial skeleton of the MOFs, thus avoiding the aggregation of the photosensitizer, which could lead to sudden inactivation. They hypothesized that the use of 2D-MOFs, i.e., MOLs, due to their two-dimensional structure, could potentially improve the efficiency of 1 O 2 diffusion generated by the photosensitizer and thus improve the efficacy of PDT.…”
Section: Application In Photodynamic Therapymentioning
confidence: 99%
“…56 As described previously, photodynamic therapy as a reliable treatment for noninvasive cancers is now receiving particular attention from researchers. 85 In the preceeding section, it was mentioned that Liu et al designed a multifunctional Hf-porphyrin NMOF nanocarrier TPZ/Hf/TCPP/PEG (Fig. 13C).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These attractive properties have made MOFs promising candidates for different applications such as sensing (biosensing, chemo-sensing, photochemical and electrochemical sensing), [3][4][5] catalysis (photocatalysis, bio-catalysis, electrocatalysis), [6][7][8] adsorption (toxic pollutant, antibiotics, and gas adsorption, wastewater treatment), [9][10][11][12] storage (gas storage, electrochemical charge storage, batteries/energy/fuel cell storage) 13 and drug delivery systems. [14][15][16][17] To obtain MOFs with desired properties for specific applications, it is important to pay attention to the synthesis route and conditions. The use of different synthesis methods at the preliminary stage is of great importance because different methods can lead to new compounds that cannot be obtained otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are composed of metal clusters or ions linked with organic moieties by forming three-dimensional (3D) or two-dimensional (2D) porous structures. MOFs and their composites are typically applied in gas capture and separation, , catalytic reactions, fluorescence sensing, semiconductive/conductive devices, and biomedical-related fields . More recently, MOFs have been studied for wastewater treatment .…”
Section: Introductionmentioning
confidence: 99%